Industrial equipment optimization for combustion performance enhancement: a real-world case study - Lin, Tianqin; Cao, Qi; Huang, Song; Zhang, Wei; Liao, Hebin; Andriukaitis, Darius; Li, Zhixiong (Frontiers in Energy Research, 2024)
To address the issue of high NOx emission from the combustion chamber, this work optimized the industrial machine structure to enhance the combustion performance. The analysis results indicated that the flue gas recirculation (FGR) could effectively reduce the combustion temperature and the distribution of high-temperature regions in the machine chamber, thereby suppressing NOx formation without affecting the gas velocity inside the chamber. Based on the simulation analysis, the FGR technology was applied to modifying the machine structure and evaluated the modification effect in real-world application. It is found that after adding FGR, the oxygen content at the furnace outlet decreased from 13.8% to 10.5%, the NOx emission from the furnace decreased from 80 mg/m3 to 18 mg/m3, and the natural gas consumption decreased by more than 17%. These results demonstrate a significant impact on energy saving and emission reduction after optimizing the machine structure, which can provide a reference basis for subsequent researchers in this field.